Rövidfilmek a magánéletről (és sérelmeiről) . Short Films About (the Invasion of) Privacy - Horgas, Ádám; Rohonyi, Gábor; Gergely, Zoltán; Fazakas, Péter
A collection of 4 short films created in the framework of the BROAD project, with the support of the Fundamental Rights and Citizenship Programme of the European Commission, dealing with the issue of privacy and the invasion of it. Ádám Horgas: “Nail Polish” (1’11”); Gábor Rohonyi: “Heavy Birthday” (1’05”); Zoltán Gergely: “Flower Power” (1’25”); Péter Fazakas: “Dreamguy” (1’11”)